Prediction of heterogeneous nucleation condensation effect on the surface of respiratory coal dust and test of dust reduction test - Hanyi LIN; Liang YUAN; Bingyou JIANG; Yuqian ZHANG; Yifan WANG; Haoyu WANG (Meitan xuebao)
Surface wettability of coal dust particles is an important factor restricting the efficiency of wet dust removal. Heterogeneous nucleation condensation on the surface of coal dust particles is a means without any pollution, without considering the surface wettability of particles, and can effectively improve the efficiency of coal dust particles being captured by droplets. Human interference with the change of temperature and humidity environment is a necessary condition to stimulate the surface nucleation condensation effect of coal dust particles. In order to obtain a quantitative prediction mathematical model for the influence of temperature and humidity conditions on the condensation effect of mine respiratory coal dust particles, based on the visualization experiment platform of particle condensation, single factor and multi-factor orthogonal experiments were carried out around three factors: initial temperature of coal dust particles, relative humidity of hot and humid gas, and temperature difference of condensation temperature. Combined with mean square error weighting method, nonlinear regression analysis method and prediction effect evaluation index, the weight proportion of each influencing factor in the condensation effect of coal dust particles was determined. Based on this, a multivariate nonlinear regression prediction model for particle condensation was constructed, and the accuracy of the model prediction was evaluated. Based on the experimental system of particle nucleation condensation and spray synergetic dust suppression, the control effects of the two synergetic and single dust suppression methods on respirable coal dust were compared and analyzed. The results show that the relative humidity of hot and humid gas has the greatest influence on the nucleation condensation effect, and the two are positively correlated, and the obvious nucleation condensation effect can be activated only when the relative humidity is greater than 70%. The influence of temperature difference on condensation effect was second only to gas relative humidity, and the condensation effect decreased first and then increased with the increase of temperature difference. The influence weight of the initial temperature of coal dust particles is the least, and the particle groups with particle size ≤ 1 μm and > 2 μm are stimulated positively and reversely, respectively. The multivariate nonlinear regression model based on the combination of various methods has better prediction accuracy and small error, and can be used to quantify the condensation effect of coal dust particles nucleation under the condition of temperature and humidity interference in a certain range. The problem of poor surface wettability of coal dust can be effectively solved by using particle nucleation condensation and spray, and the dust removal efficiency is increased by 131.84% compared with pure water spray.